Ex vivo susceptibility-weighted imaging anatomy of canine brain–comparison of imaging and histological sections - Arribarat, Germain; Cartiaux, Benjamin; Boucher, Samuel; Montel, Charles; Gros-Dagnac, Hélène; Fave, Yoann; Péran, Patrice; Mogicato, Giovanni; Deviers, Alexandra (Frontiers in Neuroanatomy, 2022)
Now that large domestic mammals are increasingly gaining access to high-field MRI, techniques that were initially developed for human patients are being used to conduct structural and functional studies of these animals’ brains. Susceptibility-weighted imaging (SWI) is a recent improvement on gradient echo imaging that affords excellent anatomical tissue contrast and a noninvasive assessment of brain iron content. The goal of the present study was to design an optimum SWI protocol for use in dogs undergoing brain MRI in a 3 tesla scanner. This protocol was applied to ex vivo brains from four dogs. It was validated by visual inspection of the SW images, which provided fine anatomical detail, as demonstrated by a comparison with corresponding microscopic sections. As resolvable brain structures were labeled, this study is the first to provide an anatomical description of SW images of the canine brain. Once validated in living animals, this SWI protocol could easily be included in routine neuroimaging protocols to improve the diagnosis of various intracranial diseases in dogs, or be used in future comparative studies to estimate brain iron content in animals.